Diseño de una metodología para la aplicación de una auditoría de gestión para el área administrativa - financiera de Astec Cia. Ltda. - Tapia Naranjo, Marco Vinicio (2013)
The implementation of a management audit to Administrative Area - Astec Financial Co.. Ltda., Helps provide an assessment of the performance (return) of this area, aimed at improving the effectiveness, efficiency and economy in the use of resources to facilitate decision making by their managers in meeting the objectives set by the Company.